From NMR Spectra to Structure - Facelli, Julio C. (2013)
This article discusses the existing methods to correlate NMR parameters describing the high resolution NMR spectra of liquids and solid systems with their structural parameters. Those methods are divided into direct and indirect ones. This article includes two types of direct methods: those based on the Nuclear Overhauser Effect (NOE) contributions to the NMR relaxation and those based on direct measurements of the dipolar couplings using several experimental approaches. Indirect methods are based on the intrinsic dependence of J couplings and shieldings on the atomic coordinates of the atoms in a molecule and its surroundings, requiring complex quantum mechanical calculations to relate NMR spectral properties to molecular and crystal structure. This article discusses how changes in chemical bonding, conformation, and stereo configurations that cause measurable changes in NMR parameters closely related to molecular and crystal structure. The final section provides information about the software and hardware required to perform calculations needed to solve structural problems using high resolution NMR. This article intends to provide molecular structural researchers new to the field of NMR, with an overall panorama of the potential of using high resolution NMR for structure elucidation, when other more traditional techniques are not feasible. To this end and to emphasize the didactic value of this work, after each section a brief conclusion has been added to recap the critical concepts.